Pelatihan Coretax Bagi Mahasiswa Universitas Mataram Sebagai Upaya Meningkatkan Literasi Perpajakan Digital - Herawati Khotmi; Baiq Anggun Hilendri Lestari; D. Tialurra Della Nabila; Suparlan; Dewi Rispawati; Rosiya Wardani; Elvina Setiawati; Yuli Astini; Eva Solina; Reny Wardiningsih; Resty Yusnirmala Dewi; Nora Listantia; Eko Supriastuti; Feryansyah (Universitas Mataram, 2026)
Digitalization of the tax system in Indonesia through the implementation of the Coretax System with a tax consultant as the speaker. It is based on the availability of human resources with sufficient digital tax expertise. The objective of this community service activity is to enhance the digital tax literacy of students at the University of Mataram through hands-on training on the use of the Coretax application. The method used was participatory training with a hands-on learning approach that involved 150 Accounting and Taxation program students. The results of the activity showed an increase in participants' understanding of Coretax features by 84.6%, as measured by pre- and post-tests. The participants also demonstrated increased confidence in operating the digital tax reporting system. The activity contributes to the formation of a digitally literate younger generation and prepares future accounting professionals to competently face the era of technology-based tax administration.